2017
DOI: 10.1021/acs.langmuir.7b01674
|View full text |Cite
|
Sign up to set email alerts
|

Unit Cell Level Thickness Control of Single-Crystalline Zinc Oxide Nanosheets Enabled by Electrical Double-Layer Confinement

Abstract: Ionic layer epitaxy (ILE) has recently been developed as an effective strategy to synthesize nanometer-thick 2D materials with a non-layered crystal structure, such as ZnO. The packing density of the amphiphilic monolayer is believed to be a key parameter that controls the nanosheet nucleation and growth. In this work, we systematically investigated the growth behavior of single-crystalline ZnO nanosheets templated at the water-air interface by an anionic oleylsulfate monolayer with different packing densities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 18 publications
1
36
0
1
Order By: Relevance
“…[ 9 ] There are only few reports in literature, which show this is possible for Wurtzite‐based materials deposited on solid substrates. [ 42–54 ] In their study on MBE (molecular beam epitaxy) of GaN on GaN substrates Xie et al. showed that a hexagonal symmetric bilayer of the cation and the anion exhibits two types of alternating step edges: [ 42 ] Edge‐Type A with two dangling bonds and Type B with only one dangling bond (Scheme 1b).…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] There are only few reports in literature, which show this is possible for Wurtzite‐based materials deposited on solid substrates. [ 42–54 ] In their study on MBE (molecular beam epitaxy) of GaN on GaN substrates Xie et al. showed that a hexagonal symmetric bilayer of the cation and the anion exhibits two types of alternating step edges: [ 42 ] Edge‐Type A with two dangling bonds and Type B with only one dangling bond (Scheme 1b).…”
Section: Introductionmentioning
confidence: 99%
“…[9] There are only few reports in literature, which show this is possible for Wurtzite-based materials deposited on solid substrates. [40][41][42][43][44][45][46][47][48][49][50][51][52] In their study on MBE (Molecular Beam Epitaxy) of GaN on GaN substrates Xie et al showed that a hexagonal symmetric bilayer of the cation and the anion exhibits two types of alternating step edges: [40] Edge-Type A with two dangling bonds and Type B with only one dangling bond (Scheme 1b). Thus, the two edge types are kinetically distinguishable.…”
Section: Introductionmentioning
confidence: 99%
“…These 2D materials can be further classified into two groups, 2D layered materials and 2D non-layered materials. Wet chemical synthesis is a common route to produce nanosheets with non-layered parent materials such as ZnO, [27,28] CuI, [29] TiO 2 , [30] SnTe, [31] Pb 1-x Sn x Se, [32] Pb 1-x Sn x Te, [33] etc. Typical 2D layered materials include graphene, hexagonal boron nitride (h-BN), [16,17,18] transition metal dichalcogenides (TMDs), [19][20][21][22][23][24][25] and bismuth oxyhalide (BiOX, X = Cl, Br and I), [26] etc., with the electronic properties varied from semimetal to insulator.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, 2D non-layered materials cannot be simply achieved by exfoliation method due to the strong covalence bonds among crystal planes. Wet chemical synthesis is a common route to produce nanosheets with non-layered parent materials such as ZnO, [27,28] CuI, [29] TiO 2 , [30] SnTe, [31] Pb 1-x Sn x Se, [32] Pb 1-x Sn x Te, [33] etc. Very recently, molecular beam epitaxial (MBE) deposition method has also been employed to produce elemental 2D materials, which is expected to be absent in nature, such as graphene's cousins, silicene, [34][35][36][37][38][39][40][41][42][43][44][45][46][47] germanene, [5,[48][49][50][51][52] phosphorene, [53,54] stanene, [55,56,57] and so on.…”
Section: Introductionmentioning
confidence: 99%